EDITORIAL - Phongsatha, Thanawan (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
The Journal of Interdisciplinary Research (JIR) is a tri-annual international journal committed to publishing high-quality, peer-reviewed articles in the field of Social Sciences. The journal serves as a platform for scholarly dialogue and the dissemination of research across various academic disciplines. Beginning with this volume, we are pleased to announce that JIR has been officially indexed in the Thai Citation Index (TCI), Tier 2. This recognition marks an important milestone in our continuous efforts to promote excellence in academic research. JIR is an open-access journal with a core objective to foster meaningful academic exchange among researchers, scholars, and students from diverse backgrounds. We strive to be a hub for interdisciplinary conversations and knowledge sharing on emerging trends and pressing issues in the global academic landscape. This volume features 15 outstanding articles contributed by researchers from different countries and academic institutions. The articles encompass a range of research methodologies—including quantitative, qualitative, and mixed-method approaches—across themes such as educational leadership, educational technology, teaching with technology, management, and learning processes. The diversity of perspectives presented reflects the journal’s commitment to cross-cultural and multi-contextual research. We extend our sincere gratitude and appreciation to all contributing researchers for their dedication to advancing knowledge that benefits society and enriches academic inquiry. The Journal of Interdisciplinary Research (JIR) will continue to support the academic community by providing a platform for publishing impactful research and fostering the exchange of ideas across disciplines. JIR publishes three issues per year: January–April (Issue 1) May–August (Issue 2) September–December (Issue 3) We welcome submissions that align with the journal’s vision of promoting interdisciplinary scholarship and addressing complex issues through collaborative research.